PENGARUH SELF ASSESSMENT SYSTEM DAN SANKSI PAJAK TERHADAP KEPATUHAN PAJAK : (Studi Kasus Pada Wajib Pajak di KPP Pratama Ambon) - Dirk Berly Tehuayo; Audry Leiwakabessy; Agustina Christina Patty (P3M Politeknik Negeri Ambon, 2023)
This research aims to examine: (1) The influence of the Self-assessment system on taxpayer compliance, (2) The influence of tax sanctions on taxpayer compliance and The population in this study are individual taxpayers registered at KPP Pratama Ambon in 2022. The sample in the research This was determined based on the purposive sampling method, data was collected by distributing questionnaires. The analysis used is multiple linear regression analysis. The test results show that 1) the self-assessment system has a significant positive effect on taxpayer compliance, 2) tax sanctions have a significant positive effect on taxpayer compliance.Keywords: Taxpayer compliance, self assessment system, tax sanctions.